2012
DOI: 10.1111/j.1754-4505.2011.00226.x
|View full text |Cite
|
Sign up to set email alerts
|

Dental treatment of patients with systemic diseases compared to patients with developmental disabilities under general anesthesia

Abstract: The medical and dental records were examined for 46 patients with systemic diseases (SD) and 75 patients with developmental disabilities (DD) aged 2-20 years, who had received dental treatment under general anesthesia (GA). Age, gender, decayed missing and filled teeth (dmft/DMFT), dental procedures, duration of GA, and posttreatment hospitalization were recorded. Before treatment, dental disease in the primary teeth was significantly higher among the group with SD (p= 0.04). In the permanent teeth, dental dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 13 publications
(26 reference statements)
3
23
0
Order By: Relevance
“…Although the duration of the operations has been specified on very few occasions in the literature, it is a variable that has been considered for classifying the dental treatment of individuals with disability under GA . It has been suggested that treatment duration is not determined by the systemic disease but rather by patient age and the type of dental procedure . As with other authors, we observed a reduction in the duration of the operations as the dental team gained experience.…”
Section: Discussionsupporting
confidence: 71%
“…Although the duration of the operations has been specified on very few occasions in the literature, it is a variable that has been considered for classifying the dental treatment of individuals with disability under GA . It has been suggested that treatment duration is not determined by the systemic disease but rather by patient age and the type of dental procedure . As with other authors, we observed a reduction in the duration of the operations as the dental team gained experience.…”
Section: Discussionsupporting
confidence: 71%
“…The disproportion of gender was noticed in most studies . It is not clearly stated why males so consistently outnumbered females.…”
Section: Discussionmentioning
confidence: 87%
“…Seventy‐one studies that included discussion of treatment under GA were found for evaluation. Among these, only 10 studies were included for the final analysis, based on the inclusion and exclusion criteria shown in Table . The majority of the studies reported on the types of dental treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many people with special health care needs can be seen at primary health care units, there is a demand for dental care under general anesthesia or sedation in the hospital environment [1][2][3][4]. The prescription of sedation or general anesthesia is linked to the impossibility of providing outpatient dental treatment due mainly to cognitive impairments, emotional conditions and complex medical conditions that require monitoring during dental treatment [1,[5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%